(untitled) (Fiep Bulletin - online, 2016)
We live in a society with high industrialization rate, triggering the excessive consumption of natural resources, occurring so high pollution rates. The theme of environmental education in schools in order to reduce the impacts of unsustainable activities to the environment, through the formation of conscientious citizens should be addressed. This study sought to encourage environmental preservation in order to develop environmental awareness combined with physical activity. This is an experimental field study. Attended by 50 students attending elementary school to high school in a school municipal network, a state and a private school in the city of Itapoá - Santa Catarina. The action was carried out in three stages: the first included storage and pet bottles of cleaning, the second the preparation of a board of "stand up paddle". The third stage was the trial of the board on the beach. The making of ecological boards showed a possibility of integrating environmental education in physical education classes. It stressed the importance of reuse and taught a new way to include it in schools as an environmental education strategy and encouraging physical activity.